Flavonoids: chemistry and biological activities - Novza, Y. A.; Popova, E. M. (Problems of Environmental Biotechnology, 2016)
In this article is described the general characteristic of flavonoids, their chemical and biological activity. The article analyses the peculiarities of flavonoids and described their importance for plant and human health.